PsAID12 provisionally endorsed at OMERACT 2018 as core outcome measure to assess psoriatic arthritis-specific health-related quality of life in clinical trials - Orbai, A; Holland, R; Leung, Y; Tillett, W; Goel, N; Christensen, R; McHugh, N; Gossec, L; De Wit, M; Højgaard, P; Coates, L; Mease, P; et al. (Journal of Rheumatology Publishing Co. Ltd, 2018)
Objective The Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) and Outcome Measures in Rheumatology (OMERACT) psoriatic arthritis (PsA) working group is developing a Core Outcome Measurement Set for PsA clinical trials [randomized controlled trials (RCT) and longitudinal observational studies (LOS)] using the OMERACT Filter 2.1 instrument selection algorithm. Our objective was to assess the Psoriatic Arthritis Impact of Disease questionnaire (PsAID12) for the measurement of the core domain PsA-specific health-related quality of life (HRQOL). Methods PsAID12 measurement property evidence gathered in a systematic literature review, and additional analyses conducted in LOS, were used to inform a consensus process. Analyses that had not been published were independently reviewed by the OMERACT technical advisory group. Data and process were presented, discussed in breakout groups, and voted on at the OMERACT conference (Terrigal, Australia, May 2018). Results PsAID12 fulfilled the green (good to go) OMERACT standards for domain match, feasibility, reliability, and construct/longitudinal construct validity. Discrimination and thresholds of meaning were amber (caution but good enough to go forward). The overall working group recommendation was amber/provisional endorsement of PsAID12 for measuring PsA-specific HRQOL in RCT and LOS. Of 96 participants who voted at the PsA OMERACT workshop, 87.5% (84) voted “yes” to endorse this recommendation; 14 of the 96 were patient research partners (PRP) and 93% of them (13) voted “yes”; 82 participants were not PRP and 87% of them (71) voted “yes.” Conclusion At OMERACT 2018, PsAID12 was the first patient-reported outcome measure provisionally endorsed as a core outcome measure for disease-specific HRQOL in PsA clinical trials. PsAID12 discrimination and improvement thresholds will be studied in future RCT.